2003
DOI: 10.1093/ndt/gfg369
|View full text |Cite
|
Sign up to set email alerts
|

Nephropathy associated with heroin abuse in Caucasian patients

Abstract: In this cohort of male Caucasian heroin addicts, HCV-associated MPGN was the most frequent pattern of nephropathy, showing that the nephropathy associated with heroin abuse in Caucasians is not of the focal and segmental glomerulosclerosis type, in contrast to previous reports on African-Americans. This aspect may have important implications for patient management and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 18 publications
1
38
0
1
Order By: Relevance
“…Furthermore, it is possible that HCV infection is a surrogate for some other factor, such as heroin use, which was not measured in our study and accounts for observed differences in renal function. However, the epidemiology of heroin-associated nephropathy has changed in recent years (48), and a study of renal biopsies in white male heroin users found that all individuals had evidence of HCV infection and the majority of renal pathologic lesions were MPGN (49). Therefore, even in individuals who may have used heroin, HCV is likely to represent an important component of renal dysfunction.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, it is possible that HCV infection is a surrogate for some other factor, such as heroin use, which was not measured in our study and accounts for observed differences in renal function. However, the epidemiology of heroin-associated nephropathy has changed in recent years (48), and a study of renal biopsies in white male heroin users found that all individuals had evidence of HCV infection and the majority of renal pathologic lesions were MPGN (49). Therefore, even in individuals who may have used heroin, HCV is likely to represent an important component of renal dysfunction.…”
Section: Limitationsmentioning
confidence: 99%
“…Renal biopsies in 19 white heroin users also demonstrated a spectrum of pathologic findings, including 13 patients with membranoproliferative glomerulonephritis (MPGN), two with chronic interstitial nephritis, two with acute proliferative glomerulonephritis, one with amyloidosis, and one with granulomatous glomerulonephritis and interstitial nephritis (119). All patients had serologic evidence of hepatitis C virus (HCV) infection, one had hepatitis B surface antigenemia, and three had HIV infection.…”
Section: Historical Perspective Of Renal Disease and Heroin Usementioning
confidence: 99%
“…La insuficiencia renal aguda se desarrolla en el 30% de los casos de rabdomiolisis. El consumo de la sustancia está implicado por la fisiopatología de la enfermedad 39,40 .…”
Section: Conclusionesunclassified